2020
DOI: 10.2147/cia.s196944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Life-Space Mobility in the Elderly: Current Perspectives</p>

Abstract: Life-space mobility (LSM) is a concept for assessing patterns of functional mobility over time. LSM is gaining traction in the research of geriatric population health. Several instruments have been developed to measure LSM, such as the University of Alabama at Birmingham Life-Space Assessment (LSA) or the Nursing Home Life-Space Diameter instrument. There has been exponential growth in the use of instruments measuring LSM in studies of older adults since the concept was introduced in 1985. In response to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 82 publications
(83 reference statements)
2
74
1
4
Order By: Relevance
“…Of the four groups, Group 3 residents started with the widest LS but progressed to a substantial decline over time. Compared to Group 2, residents in Group 3 were younger and had better physical performance at baseline, characteristics positively associated with LS in NH residents [ 26 , 28 , 29 ] and community-dwelling older adults [ 7 , 11 ]. LS in NHs is strongly determined by daily routines and activities [ 26 ], which should facilitate a stable wide LS in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four groups, Group 3 residents started with the widest LS but progressed to a substantial decline over time. Compared to Group 2, residents in Group 3 were younger and had better physical performance at baseline, characteristics positively associated with LS in NH residents [ 26 , 28 , 29 ] and community-dwelling older adults [ 7 , 11 ]. LS in NHs is strongly determined by daily routines and activities [ 26 ], which should facilitate a stable wide LS in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined LS and its associated characteristics in community-dwelling older adults. These indicate that restricted LS is associated with older age, more severe depression, apathy, comorbidity, cognitive impairment, impairments in physical performance, and environmental barriers [ 7 , 11 15 ]. Further, restricted LS can predict healthcare utilization [ 16 ], nursing-home (NH) admission [ 17 ], falls [ 18 ], and mortality [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This association between frequent driving and increased social functioning is particularly relevant since active engagement in social activities is a key component of successful aging (Cosco et al, 2013;Fazeli et al, 2020). Previous studies measuring mobility and life space, or the size of a person's physical and social environment, have shown that limited life space is associated with older age, low income, and rural residence (Johnson et al, 2020;Peel et al, 2005). Further, people lacking driving mobility are less likely to travel within and beyond their city (i.e., have limited life space), whether due to age-related physical limitations, less access to public transportation, or lack of disposable income for activities (Peel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since the concept of LSM was introduced in 1985 by May [ 10 ], it is increasingly being used to characterize the status or time course of LSM impairment, or to initiate, adjust and evaluate therapies or interventions. Several instruments have been developed to measure LSM in older adults [ 11 ]; however, with a focus on community-dwelling older persons [ 12 ].…”
Section: Introductionmentioning
confidence: 99%